Answer:
Case 1
both m and n are even
Therefore m/2 and n/2 are integers
Then,
m-n
=2(m/2 - n/2)
Since m/2 and n/2 are integers
Then m/2 - n/2 will be an integer
Therefore,
m-n = 2(Z)
Where Z is an integer
Since 2 is a factor of m-n
Therefore m -n is even
Case 2
Both m and n are odd
m-n
= 2(½m - ½n)
When an odd number is divided by 2 it gives an integer and a remainder of 1
Therefore
½m = Y + ½
And
½n = Z + ½
Where Y and Z are integers
Then
m-n = 2(Y+½-Z-½)
= 2(Y-Z)
Y-Z will also be an integer
m-n= 2A
Therefore m-n is even
Case 3
One is odd and the other even
m-n = 2(m/2 - n/2)
Assume m is even and n is odd
From the discussions above
m-n = 2(Y - Z - ½)
m-n = 2(A - ½)
Hence m-n is not even because when is divided by two it doesn't give an integer.
Therefore for all integers m and n, m - n is even if, and only if, both m and n are even or both m and n are odd.